الاختصاص العالمي كالية لمكافحة الجريمة الدولية - غازي زامل, صهيب سهيل; بوشاشية, شهرزاد (Université de M'sila, 2019)
يلجأ المجرمون بعد الانتهاء من ارتكابهم لأفعال إجرامية ،البحث عن منفذ قانوني للإفلات من العقاب وذلك من خلال الهروب من البلد الذي تشكل فيها جزء من الجريمة ،إلى بلد آخر يعبر مبدأ الاختصاص الجنائي العالمي على تطبيق القانون الجنائي للدولة على الجرائم الدولية بصرف النظر عن مكان وقوعها وأيا كانت جنسية مرتكبها أو جنسية المجني عليه وهذه القدرة تمنح أهمية بالغة لمكافحة الجريمة الدولية ، ومن الطبيعي ألا يطبق هذا المبدأ على كل الجرائم ، إذ يؤدي ذلك إلى تنازع خطير بين التشريعات الجنائية للدول المختلفة ، لذلك يقتصر تطبيقه على مجموعة من الجرائم تهم المجموعة الدولية كلها، بحيث يعد مرتكبها متعديا على مصلحة مشتركة لكل الدول ومن بينها الدول التي قُبض على الجاني فيها . After the completion of their criminal acts, the criminals seek to find a legal outlet for impunity by escaping from the country in which they form part of the crime to another country which expresses the principle of universal criminal jurisdiction to apply the criminal law of the State to international crimes regardless of where they occur Whatever the nationality of the perpetrator or the nationality of the victim, this capacity is of great importance for combating international crime. Naturally, this principle is not applied to all crimes. This leads to a serious conflict between the criminal legislation of different States. All of which are deemed to be mutually prejudicial to all States, including the States in which the offender was arrested
Keywords: الاختصاص الجريمة العالمي